The first record of genus Suwallia Ricker, 1943 (Plecoptera: Chloroperlidae) from China - Li, Weihai (Illiesia, 2015)
The chloroperline stonefly genus Suwallia is reported from China for the first time from the Inner Mongolia Autonomous Region. A supplementary description is provided for the identification of Suwallia teleckojensis (Šámal 1939).
Keywords: entomology; stoneflies; Perlodidae; Plecoptera; Suwallia teleckojensis; Mongolia